1977
DOI: 10.5254/1.3535145
|View full text |Cite
|
Sign up to set email alerts
|

Elastomer Blend Properties—Influence of Carbon Black Type and Location

Abstract: Criteria for minimizing hysteresis in carbon-black-filled elastomer blends are: (1) large black unit size, wide distribution, and low structure; (2) higher black loading in the discrete polymer phase (large zones); and (3) polymer of lower hysteresis as the continuous phase (low black loading). Of the different strength properties that were evaluated, tear and fatigue resistance showed the greatest dependence on black location in NR-BR and NR-SBR blends. Both properties were markedly higher for NR-BR, with mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…The sol–gel reaction of TEOS involves the swelling of a precured rubber in TEOS and then subjection of the TEOS‐swollen rubber to a sol–gel process, that is, hydrolysis and condensation. This application of the sol–gel process to rubber chemistry is somewhat related to the use of silane coupling agents and moisture or silane curing,27 and it has been carried out already on silicon rubber 28. The TEOS contained in the rubber is converted into silica upon hydrolysis and condensation according to the following equation: …”
Section: Resultsmentioning
confidence: 99%
“…The sol–gel reaction of TEOS involves the swelling of a precured rubber in TEOS and then subjection of the TEOS‐swollen rubber to a sol–gel process, that is, hydrolysis and condensation. This application of the sol–gel process to rubber chemistry is somewhat related to the use of silane coupling agents and moisture or silane curing,27 and it has been carried out already on silicon rubber 28. The TEOS contained in the rubber is converted into silica upon hydrolysis and condensation according to the following equation: …”
Section: Resultsmentioning
confidence: 99%
“…Physical properties of rubber vulcanizates are improved by reinforcing with fillers such as carbon black and silica 1–4. The reinforcement by filler enhances the physical properties of hardness, modulus, tensile strength, abrasion resistance, etc.…”
Section: Introductionmentioning
confidence: 99%
“…This can be attributed to the fact that the SBR forms the continuous phase in this blend. Consistently, Hess and Chirico observed that SBR is the continuous phase in 50/50 blends of NR/SBR. As the two‐phase morphology of the polymer blend is dominated by many parameters such as the molecular weight of the blend constituents and their viscosities, in addition to the blend composition, the observed morphological behavior is understandable.…”
Section: Resultsmentioning
confidence: 99%